Pengaruh Gaya Kepemimpinan Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada PT.Indosurya Kencana Bekasi - Dela Rosa; Herlina Febriyanti; Maimunah (Jurnal Ekonomi dan Bisnis Digital, 2022)
The attainment of high performance is a desirable objective for every organization. The significance of leadership within an organization cannot be overstated, as it plays a crucial role in ensuring the smooth functioning of the management process and fostering employee enthusiasm towards their job responsibilities. Enhancing work discipline is undoubtedly a challenging endeavor. However, in order to address this issue, a leader can effectively guide their employees by providing illustrative instances and clear instructions that elucidate the regulations outlined within the organization. In order to achieve the desired organizational objectives within an increasingly competitive corporate landscape, it is imperative for a company to possess employees who exhibit exceptional performance. Performance can be defined as the outcome of an employee's efforts in terms of both the quality and quantity of work accomplished, aligned with the assigned responsibilities. The study employed a quantitative research methodology, incorporating an analysis of validity and reliability tests. This study focuses on the population of employees at PT Indosurya Kencana Bekasi who have completed their education at either a high school or vocational high school level, a Diploma 3 (D3) level, or a Strata 1 (S1) level. This study utilized a sample size of 96 employees from PT Idosurya Kencana Bekasi. The educational background of the respondents from PT Indosurya Kencana Bekasi, consisting of 96 employees, reveals that 61 employees have completed their education up to the level of Senior High School (SMA) or Vocational School (SMK). Additionally, 21 employees have obtained a Diploma 3 (D3) degree, while 14 employees have completed their education up to the level of Bachelor's degree (Strata 1 or S1). This implies that the attainment or non-attainment of organizational objectives is primarily influenced by an individual's leadership approach in effectively managing available resources, and it is through this leadership style that the ambiance of the workplace is established. Work discipline can be characterized as a mindset encompassing respect, gratitude, compliance, and adherence to established regulations, both explicit and implicit. It entails the ability to consistently adhere to these rules and fulfill assigned responsibilities without evading accountability, even in the face of potential penalties for non-compliance. Performance management encompasses the comprehensive undertaking aimed at enhancing the performance of a company or organization, encompassing the performance of both individuals and work groups within the company.